2007
DOI: 10.2753/pss0885-3134270201
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving Emotion in the Buyer–Seller Interchange: The Moderated Impact on Performance

Abstract: This research focuses on the salesperson's ability to perceive emotions in the buyer-seller interaction. Drawing on the emotional ability literature, the authors develop hypotheses within a conceptual framework of salespeople's ability to perceive the emotions of customers, and examine how this ability influences the relationships between selling behaviors and performance. Findings indicated that the ability to accurately appraise the emotions of others moderated the practice of adaptive selling and customer-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 35 publications
3
66
0
Order By: Relevance
“…Customer emotions are a better source for predicting their future behavior intention in contrast to customer satisfaction (Koenig-Lewis & Palmer, 2008). The correct judgment of customers' perceived emotions by the sales force will strengthen the buyer-seller relationship and enhance selling performances (Kidwell et al, 2007). In impulse buying, the emotional satisfaction of consumers has a significant positive relation with buying behavior and purchase in developing nations (Dhurup, 2014).…”
Section: Role Of Emotional Values In Buying Decisionmentioning
confidence: 99%
“…Customer emotions are a better source for predicting their future behavior intention in contrast to customer satisfaction (Koenig-Lewis & Palmer, 2008). The correct judgment of customers' perceived emotions by the sales force will strengthen the buyer-seller relationship and enhance selling performances (Kidwell et al, 2007). In impulse buying, the emotional satisfaction of consumers has a significant positive relation with buying behavior and purchase in developing nations (Dhurup, 2014).…”
Section: Role Of Emotional Values In Buying Decisionmentioning
confidence: 99%
“…We received responses from 106 salespeople and 77 back-office employees, for response rates of 50.7% and 26.1%, respectively. Although the back-office employees' response rate was lower, both these rates still compare favourably with previous research using similar samples (e.g., Hancer and George, 2003;Kidwell et al, 2007). Management also noted at the start of the data collection To link the 106 salespeople and 77 back-office employees, we asked each participant to identify one member from the opposite group with whom they collaborated most when working on customer orders.…”
Section: Participants and Proceduresmentioning
confidence: 51%
“…Emotional intelligence also influences job-related outcomes, such that Kidwell et al (2007Kidwell et al ( , 2011 and McFarland et al (2016) find that emotionally intelligent salespeople effectively apply customer-oriented selling strategies and thereby increase their sales performance.…”
Section: Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though supervisory control has been extensively researched, the findings are still inconclusive (Fang, Evans, & Zou, 2005;Flaherty, Arnold, & Hunt, 2007). Besides, past studies examining the salesperson's adaptive selling behavior (ASB) and salesperson performance have also reported inconsistent or mixed results, while a majority of the studies reported results supporting the positive relationship between the salesperson's ASB and salesperson performance (Kidwell, McFarland, & Avila, 2007;Spiro & Weitz, 1990). Due to the observed inconsistencies and mixed results reported in the relationship between the supervisory control and salesperson performance, as well as the relationship between salesperson's adaptive selling behaviour and salesperson performance, this study propose to introduce salesperson's adaptive selling behaviour as a mediator with the aim of filling the gaps on the above mentioned.…”
Section: Introductionmentioning
confidence: 77%